Negative electrode for lithium secondary battery and negative electrode manufacturing device
By using magnetic field orientation and photothermal drying technology in the negative electrode manufacturing process of lithium secondary batteries, the problem of high orientation and uniform arrangement of carbon-based negative electrode active materials in the negative electrode active layer is solved, and the charging and discharging performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202480003338.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-13
- Filing Date
- 2024-03-11
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to achieve high orientation and uniform arrangement of carbon-based negative electrode active materials (such as graphite) in the negative electrode active layer of lithium secondary batteries, resulting in poor charging performance of the battery.
Using a manufacturing device including an orientation member and a drying member, by applying a magnetic field to the negative electrode slurry coated on the electrode sheet, and drying with light and thermal energy in different steps, ensuring that the crystal surfaces of the carbon-based negative electrode active material are evenly arranged in the negative electrode active layer at a high angle.
The high orientation and uniform arrangement of carbon-based negative electrode active materials in the negative electrode active layer are achieved, and the charging and discharging performance of lithium secondary batteries is improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention claims the benefit of priority based on Korean Patent Application No. 10-2023-0032299, filed on Mar. 13, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a negative electrode for a lithium secondary battery and a manufacturing device for manufacturing the negative electrode. Background Art
[0003] Recently, secondary batteries are widely used not only in small-sized devices such as portable electronic devices but also in large and medium-sized devices such as battery packs or energy storage devices for hybrid vehicles or electric vehicles.
[0004] This secondary battery is a chargeable and dischargeable power generation device comprising a stacked structure of a positive electrode / separator / negative electrode. Generally, the positive electrode contains lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based negative electrode active material such as graphite. When the secondary battery is charged, lithium ions released from the positive electrode are adsorbed into the carbon-based negative electrode active material of the negative electrode. When the secondary battery is discharged, lithium ions contained in the carbon-based negative electrode active material are adsorbed into the lithium metal oxide of the positive electrode, and charging and discharging are repeated.
[0005] In this case, the negative electrode active material used for the negative electrode contains a graphite material such as natural graphite. Graphite has a layered structure formed by stacking multiple layers of carbon atoms to form a planar unfolded network structure. During charging, lithium ions can invade from the edge of these graphite layers (the side where these layers overlap) and diffuse between these layers, and during discharge, lithium ions can be dissociated and released from the edge of the graphite layer. In addition, since the resistance of graphite in the lateral direction of the layer is lower than the resistance in the layer stacking direction, a conduction path for transferring electrons is formed along the lateral direction of the layer.
[0006] In this regard, in lithium secondary batteries using graphite, a technique for magnetically orienting the graphite contained in the negative electrode to improve the charging performance of the negative electrode has conventionally been proposed. Specifically, the configuration of the technique is that when the negative electrode is formed, the graphite (0,0,2) crystal plane is oriented so that it is approximately horizontal relative to the current collector in the magnetic field and fixed therein. In this case, since the edge of the graphite layer faces the positive electrode active layer, the insertion and dissociation of lithium ions can proceed smoothly, shortening the conduction path of the electrons, thereby improving the electronic conductivity of the negative electrode, thereby improving the charging performance of the battery.
[0007] Meanwhile, the negative electrode slurry used to manufacture the negative electrode active layer of the lithium secondary battery has the form of a mixture of graphite (carbon-based negative electrode active material) and a dispersant. In this case, water is generally used as a dispersant. Water is a solvent with a large surface tension, and the negative electrode slurry contained therein will show a phenomenon of reduced surface area exposed to the air after being coated on the negative electrode current collector due to the large surface tension of water. Therefore, the negative electrode slurry coated on the negative electrode current collector forms a curved surface with edge ends at a predetermined angle to the surface of the negative electrode current collector toward the inside of the slurry. Due to the large surface tension of water, the curved surface causes the potential energy of the molecules near the liquid surface and the molecules inside the liquid to be different, and this energy deviation may increase the kinetic energy of the components contained in the negative electrode slurry. The increase in the kinetic energy of these components is a factor that hinders the use of magnetic field orientation of graphite.
[0008] Specifically, by applying a magnetic force greater than the kinetic energy of graphite, the graphite crystal plane is rotated, thereby achieving the orientation of the graphite crystal plane by the magnetic force. However, at the edge of the negative electrode slurry, the molecules close to the liquid surface have different energy from the molecules inside the liquid, which leads to an increase in the kinetic energy of the graphite contained in the edge. Therefore, when a magnetic field is applied to the front surface of the negative electrode slurry, the central graphite of the negative electrode slurry with a flat exposed surface has a high orientation, while the graphite at the edge of the negative electrode slurry with a curved exposed surface has a low orientation.
[0009] Therefore, a technology is needed that can improve the low orientation of graphite caused by the curved surface structure caused by the edge of the negative electrode slurry, so as to manufacture a negative electrode active layer in which the graphite crystal planes are uniformly arranged at a high angle relative to the current collector surface. Summary of the invention
[0010] Technical issues
[0011] The present invention aims to provide a negative electrode manufacturing technology in which a carbon-based negative electrode active material (such as graphite) contained in a negative electrode active layer has a high orientation, and this orientation is achieved uniformly.
[0012] Technical Solution
[0013] In order to solve the above problems,
[0014] In one embodiment, the present invention provides:
[0015] A negative electrode manufacturing device for a lithium secondary battery, comprising: an orientation component for applying a magnetic field to the upper and lower parts of an electrode sheet whose surface is coated with a negative electrode slurry containing a carbon-based negative electrode active material; and a drying component for drying the negative electrode slurry of the electrode sheet to which the magnetic field is applied by the orientation component;
[0016] The drying component includes a first drying component and a second drying component. The first drying component pre-dries the edge of the negative electrode slurry when the orientation component applies a magnetic field to the electrode sheet. The second drying component dries the entire surface of the negative electrode slurry after the orientation component completes the magnetic field application.
[0017] Here, the orientation member may include a first magnet member disposed on an upper portion of the electrode sheet and a second magnet member disposed on a lower portion of the electrode sheet.
[0018] The first magnet member and the second magnet member may include a plurality of unit magnets disposed along a conveyance direction (x-axis direction) and a width direction (y-axis direction) of the electrode sheet.
[0019] In addition, the length of the first magnetic component and the second magnetic component along the conveying direction of the electrode sheet may be 0.5m to 10m; the ratio of the length in the width direction to the length in the width direction of the negative electrode slurry may be 105 to 150%.
[0020] Furthermore, the first drying member may be disposed alone at a widthwise edge of the magnet member along the conveying direction of the electrode sheet, or may be disposed mixed with the unit magnets in a row at a widthwise edge of the magnet member.
[0021] In addition, the first magnet component and the second magnet component can be divided into a first area where the length ratio of the magnet component is 0% to 10%, a second area where the length ratio of the magnet component is 10% to 90%, and a third area where the length ratio of the magnet component is 90% to 100% based on the point where the electrode sheet is introduced along the conveying direction of the electrode sheet, and the first drying component can be set in the second area of any one of the first magnet component and the second magnet component.
[0022] In addition, the first drying part may include at least one of an ultraviolet drier, a near infrared drier, and a far infrared drier.
[0023] In addition, the second drying part may be disposed adjacent to an end of the orientation part that moves out the electrode sheet to which the magnetic field is applied.
[0024] In addition, the second drying part may include one or more of a thermal dryer, a vacuum oven, and a heater.
[0025] In addition, in one embodiment, the present invention provides a negative electrode for a lithium secondary battery manufactured by the manufacturing apparatus of the present invention, comprising: a negative electrode collector, and a negative electrode active layer, wherein the negative electrode active layer is arranged on at least one side of the negative electrode collector and contains a carbon-based negative electrode active material.
[0026] In this case, the negative electrode active layer is divided into: a flat area with uniform thickness located in the center; and a landslide area with a thickness gradient located at the edge of the negative electrode active layer in the width direction of the negative electrode active layer, wherein the flat area and the landslide area can satisfy the following formula 1:
[0027] [Formula 1]
[0028] 0.9≤[OI 滑坡 ] / [OI 中心 ]≤1.3
[0029] Among them, in formula 1,
[0030] OI 滑坡 represents the ranking value (OI) of the landslide area,
[0031] OI 中心 Indicates the alignment value (OI) of the flat area,
[0032] The arrangement value (OI) represents the area of the peak representing the (0,0,4) crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) ratio (I 004 / I 110 ).
[0033] Here, the arrangement value of the flat area of the negative electrode active layer (OI 中心 ) can be from 0.1 to 1.5.
[0034] In addition, the flat area of the negative electrode active layer may account for more than 95% of the total length of the negative electrode active layer in the width direction, and the landslide area of the negative electrode active layer may account for less than 5% of the total length of the negative electrode active layer in the width direction.
[0035] In addition, the carbon-based negative electrode active material contained in the negative electrode active layer may include at least one of natural graphite and artificial graphite.
[0036] Beneficial Effects
[0037] By setting a drying component using light energy at the width direction edge of the magnetic component that orients the crystal plane of the carbon-based negative electrode active material, the negative electrode manufacturing device for lithium secondary batteries of the present invention can simultaneously align the crystal planes and pre-dry the carbon-based negative electrode active material at the edge end of the negative electrode slurry.
[0038] Therefore, the negative electrode manufactured in this way can achieve high orientation of the crystal plane of the carbon-based negative electrode active material contained in the landslide area of the negative electrode active layer, thereby showing excellent overall orientation and orientation uniformity of the negative electrode active layer. In addition, the lithium secondary battery having the negative electrode has the advantage of excellent charge and discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a structural diagram schematically showing the structure of the negative electrode manufacturing apparatus of the present invention.
[0040] Figure 2 It is a cross-sectional view of the negative electrode manufacturing apparatus in the width direction (y-axis direction), which shows the magnetic field M of the first magnet component; and the direction in which the heat energy E of the second drying component introduced at the edge side of the first magnet component acts on the negative electrode slurry.
[0041] Figure 3 and Figure 4 They are perspective views showing the position and form of the first drying part, respectively. DETAILED DESCRIPTION
[0042] The present invention can have various modifications and various embodiments, so specific embodiments thereof will be described in detail below.
[0043] However, it should be understood that the present invention is not limited to the specific embodiments, but includes all modifications, equivalents or substitutes within the spirit and technical scope of the present invention.
[0044] The terms "including" or "having" used herein are used to specify the presence of features, numbers, steps, operations, components or elements or a combination thereof, and it should be understood that there is no possibility of excluding the presence or addition of one or more other features, numbers, steps, operations, components, elements or a combination thereof in advance.
[0045] Furthermore, in the present invention, when a part of a layer, film, region, plate, etc. is placed "on" another part, this includes not only a case where the part is placed "directly" "on" another part, but also a case where the other part is disposed therebetween. Conversely, when a part of a layer, film, region, plate, etc. is placed "under" another part, this includes not only a case where the part is placed "directly" "on" another part, but also a case where the other part is disposed therebetween. Furthermore, in the present invention, "on" may include not only a case where it is placed on an upper part, but also a case where it is placed on a lower part.
[0046] In addition, in the present invention, "comprising as a main component" may refer to a defined component comprising at least 50% by weight (or at least 50% by volume), at least 60% by weight (or at least 60% by volume), at least 70% by weight (or at least 70% by volume), at least 80% by weight (or at least 80% by volume), at least 90% by weight (or at least 90% by volume), or at least 95% by weight (or at least 95% by volume) relative to the total weight (or total volume) of the negative electrode active material. For example, "comprising graphite as a main component of the negative electrode active material" may refer to graphite containing at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% by weight based on the total weight of the negative electrode active material, and in some cases, may refer to all negative electrode active materials being graphite, including 100% by weight of graphite.
[0047] In addition, as used herein, “electrode sheet” may refer to an object in which a negative electrode slurry is coated on a negative electrode collector, or an object in which a negative electrode slurry is coated on a negative electrode collector and dried to form a negative electrode active layer.
[0048] In addition, as used herein, "carbon-based negative electrode active material orientation" or "carbon-based negative electrode active material arrangement" refers to the distribution of the crystal planes of the carbon-based negative electrode active material containing the negative electrode active material particles in a predetermined orientation relative to the surface of the negative electrode current collector. In this case, the crystal plane is a crystal plane representing the planar structure of the carbon-based negative electrode active material, which may refer to a (1,0,0) crystal plane or a (1,1,0) crystal plane. In addition, "orienting the carbon-based negative electrode active material" may be different from the carbon-based negative electrode active material particles themselves being arranged to have a specific orientation within the negative electrode active layer.
[0049] In addition, "high orientation (or orientation degree) of carbon-based negative electrode active materials" may refer to the carbon-based active materials contained in the negative electrode active layer being arranged at a high frequency relative to the surface of the negative electrode current collector. In some cases, it may refer to the carbon-based active materials contained in the negative electrode active layer being arranged at a high angle relative to the surface of the negative electrode current collector (for example, greater than 45°; more specifically, above 60°).
[0050] In addition, "a high degree of arrangement of carbon-based negative electrode active materials" may refer to "OI" described herein having a large value, so that the carbon-based negative electrode active materials contained in the negative electrode active layer are arranged at a low angle (e.g., less than 45°) relative to the surface of the negative electrode current collector. Conversely, "a low degree of arrangement of carbon-based negative electrode active materials" may refer to "OI" having a small value, indicating that the carbon-based negative electrode active materials contained in the negative electrode active layer are arranged at a high angle (e.g., greater than 45°; more specifically, greater than 60°) based on the surface of the negative electrode current collector.
[0051] In addition, as described herein, the term "crystal plane of carbon-based negative electrode active material" may refer to a plane where the atoms of the carbon-based negative electrode active material form a crystal shape. In the present invention, it may refer to a crystal plane containing the plane of the carbon-based negative electrode active material, or a crystal plane containing the a-axis / ab-axis of the carbon-based negative electrode active material crystal.
[0052] Hereinafter, the present invention will be described in more detail.
[0053] Negative electrode manufacturing device for lithium secondary battery
[0054] In one embodiment, the present invention provides a negative electrode manufacturing device for a lithium secondary battery, comprising:
[0055] an orientation member for applying a magnetic field to an upper portion and a lower portion of an electrode sheet having a surface coated with a negative electrode slurry containing a carbon-based negative electrode active material; and
[0056] A drying unit for drying the negative electrode slurry of the electrode sheet to which the magnetic field is applied by the orientation unit,
[0057] Wherein, the drying component comprises a first drying component and a second drying component,
[0058] Wherein, the first drying component pre-dries the edge of the negative electrode slurry when the orientation component applies a magnetic field to the electrode sheet,
[0059] The second drying component dries the entire surface of the negative electrode slurry after the orientation component completes applying the magnetic field.
[0060] The negative electrode manufacturing device of the present invention is a device for manufacturing a negative electrode used in a lithium secondary battery, which can arrange the crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry at a high angle close to vertical relative to the negative electrode collector by applying a magnetic field to the negative electrode slurry (specifically, a carbon-based negative electrode active material) contained in the surface of the negative electrode current collector and coated on the negative electrode current collector. In this case, the negative electrode manufacturing device can not only arrange the carbon-based negative electrode active material contained in the negative electrode slurry to be highly oriented, but also has the advantage of being conducive to the orientation of the carbon-based negative electrode active material even at the edge end of the negative electrode slurry where the carbon-based negative electrode active material is difficult to arrange (in other words, the landslide area of the negative electrode active layer). Therefore, the negative electrode manufacturing device can achieve uniform arrangement of the carbon-based negative electrode active material contained in the negative electrode slurry.
[0061] To this end, the negative electrode manufacturing apparatus includes an orientation unit for aligning the crystal planes of the carbon-based negative electrode active material contained in the negative electrode slurry and a drying unit for drying the negative electrode slurry.
[0062] Figure 1 Schematically shows the structure of the negative electrode manufacturing device of the present invention. Figure 1The structure of the negative electrode manufacturing device 10 includes: an orientation component 110: 110a and 110b, which is used to apply a magnetic field to the upper and lower parts of the electrode sheet along the conveying direction of the electrode sheet (x-axis direction); and a drying component 120, which is used to dry the negative electrode slurry of the electrode sheet to which the magnetic field is applied by the orientation component.
[0063] The orientation components 110: 110a and 110b are respectively disposed at the upper and lower portions of the electrode sheet being conveyed to apply a magnetic field to the exposed surface of the negative electrode slurry S and the exposed surface of the negative electrode collector C of the electrode sheet. In this case, the orientation components 110: 110a and 110b include a first magnet component 110a and a second magnet component 110b disposed at the upper and lower portions of the electrode sheet, respectively, so that when a magnetic field is applied to the negative electrode slurry S coated on the negative electrode collector C and conveyed, the magnetic field is uniformly applied to the side of the electrode sheet where the negative electrode slurry S is exposed (i.e., the upper surface) and the side of the electrode sheet where the negative electrode collector C is exposed (i.e., the lower surface).
[0064] In this case, compared with the case where the magnet component is only arranged on the upper surface of the electrode sheet (inclination of the carbon-based negative electrode active material: about 40°-50°), the inclination of the crystal plane of the carbon-based negative electrode material relative to the negative electrode collector C may increase, and therefore, the inclination of the crystal plane of the carbon-based negative electrode active material relative to the surface of the negative electrode collector C may have an angle close to vertical.
[0065] In addition, the first and second magnet parts 110a and 110b may include unit magnets 111a and 111b, respectively, and support parts 112a and 112b for fixing the unit magnets.
[0066] The unit magnets of the first magnet component 110a and the second magnet component 110b may each include a large-area unit magnet; or Figure 3 and Figure 4 As shown, when the direction of the electrode sheet coated with the negative electrode slurry S is defined as the x-axis direction, and the width direction of the transferred electrode sheet is defined as the y-axis direction, the first magnet component 110a and the second magnet component 110b may include a plurality of small-area unit magnets in the x-axis direction and the y-axis direction, respectively. In this case, the unit magnet may include (where m is an integer greater than 2) and n pieces (where n is an integer greater than 2) in the x-axis direction and the y-axis direction, respectively, to form a magnet array, so one magnet component may include m×n pieces of unit magnets.
[0067] In addition, the unit magnet may include an electromagnet and / or a permanent magnet. The electromagnet may include a DC electromagnet and an AC electromagnet. In addition, the permanent magnet may include a magnet having ferromagnetic properties and a magnet having soft magnetic properties, including NdFeB-based magnets, SmCo-based magnets, ferrite magnets, Alnico magnets, FeCrCo-based magnets, bonded magnets (Nd-Fe-B-based, Sm-Fe-N-based, Sm-Co-based, ferrite-based), etc.
[0068] In addition, the unit magnets of the first magnetic component 110a and the second magnetic component 110b can be arranged so that the unit magnets have opposite magnetic poles. The N poles of the unit magnets of the first magnetic component 110a and the S poles of the unit magnets of the second magnetic component 110b can face each other; or the unit magnets can be arranged so that the S poles of the unit magnets of the first magnetic component 110a and the N poles of the unit magnets of the second magnetic component 110b face each other. In this way, when the electrode sheet passes through the space between the unit magnets with opposite magnetic poles, an attractive force is generated between the first magnetic component 110a and the second magnetic component 110b. Since the crystal planes of the carbon-based negative active material contained in the negative electrode slurry S are arranged in the direction of the attractive force, the crystal planes of the carbon-based negative active material are arranged at a larger angle relative to the current collector C (or electrode sheet).
[0069] In addition, the spacing distance between the first magnetic component 110a and the second magnetic component 110b can be 10 mm to 50 mm, more specifically, 10 mm to 40 mm; 20 mm to 50 mm; or 15 mm to 45 mm. The present invention can more efficiently arrange the crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry S with less energy by adjusting the spacing distance between the first magnetic component 110a and the second magnetic component 110b to the above range.
[0070] In addition, the first magnet component 110a and the second magnet component 110b may have a predetermined length along the conveying direction of the electrode sheet, so that the magnetic field necessary for aligning the crystal planes of the carbon-based negative electrode active material contained in the negative electrode slurry S at a high angle relative to the negative electrode collector C can be fully applied. Specifically, the length of the first magnet component 110a and the second magnet component 110b along the conveying direction of the electrode sheet may be 0.5m to 10m, and more specifically, their lengths may be 0.5m to 7.5m; 0.5m to 5m; 0.5m to 2.5m; 1m to 5m; 3m to 8m; 6m to 10m; or 4m to 9m.
[0071] In addition, the dimensions of the first magnet component 110a and the second magnet component 110b in the width direction (y-axis direction) may be adjusted to be larger than the dimensions of the negative electrode slurry S in the width direction (y-axis direction). For example, based on the length of the negative electrode slurry S in the width direction, the length ratio of the first magnet component 110a and the second magnet component 110b in the width direction may be 105% to 150%. More specifically, based on the length of the negative electrode slurry S in the width direction, the length ratio may be 110% to 150%; 110% to 130%; 110% to 120%; 105% to 120%; 130% to 150%; 105% to 120%; or 105% to 110%. Refer to Figure 2 A magnetic field is uniformly applied between the first magnetic component 110a and the second magnetic component 110b along a magnetic field direction perpendicular to the surface of the electrode sheet.
[0072] In this case, when the length of the first magnetic component 110a and the second magnetic component 110b is the same as the length ratio of the negative electrode slurry applied to the electrode sheet and / or the electrode sheet, it is difficult to fully overcome the intermolecular energy deviation generated at the edge of the slurry due to the surface tension of the negative electrode slurry solvent, and therefore, it is difficult for the crystal plane of the carbon-based negative electrode active material to be arranged at a high angle relative to the negative electrode current collector. However, by satisfying the above range of the width direction length of the first magnetic component 110a and the second magnetic component 110b, as shown in Figure 2 As shown, since a magnetic field M in the same direction as the center S1 of the negative electrode slurry S can be strongly applied to the edge S2, the present invention can achieve a high degree of orientation of the carbon-based negative electrode active material G distributed at the edge S2 of the negative electrode slurry S in the form of a curved surface.
[0073] In addition, the drying part 120 functions to fix the carbon-based negative active material arranged by the alignment parts 110 : 110 a and 110 b by drying the negative electrode slurry S.
[0074] In this case, the drying part 120 includes: a first drying part 121, which is used to pre-dry the edge end S2 of the negative electrode slurry when the orientation parts 110: 110a and 110b apply a magnetic field to the electrode sheet; and a second drying part 122, which is used to dry the entire surface of the negative electrode slurry S after the magnetic field application of the orientation parts 110: 110a and 110b is completed.
[0075] When the orientation parts 110: 110a and 110b apply a magnetic field to the negative electrode slurry, the first drying part 121 selectively applies light energy only to the edge end S2 of the negative electrode slurry for pre-drying, thereby fixing the crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry simultaneously or immediately after orientation.
[0076] To this end, the first drying unit 121 may be disposed on one or more sides of the first and second magnet units 110a and 110b, and may further include a device for irradiating light or applying light of a specific wavelength to the surface of the negative electrode slurry.
[0077] Typically, the negative electrode slurry is dried by applying high-temperature hot air, which can result in a long drying time for the negative electrode slurry, thereby destroying the arrangement of the carbon-based negative electrode active material in the negative electrode slurry. In addition, if the speed of the hot air is reduced and the heat is increased to solve these problems, the solvent in the negative electrode slurry tends to dry relatively quickly on the surface of the negative electrode slurry. This phenomenon causes the solvent present inside the negative electrode slurry to migrate to the surface and volatilize. This migration of the solvent causes the binder inside the negative electrode slurry to concentrate on the surface of the negative electrode slurry, thereby reducing the adhesion strength of the negative electrode active layer to the negative electrode current collector. However, the present invention can quickly fix the carbon-based negative electrode active material with oriented crystal planes without losing the degree of orientation by selectively applying light energy instead of heat energy only to the edge end of the negative electrode slurry.
[0078] Therefore, the first drying part 121 may include a device that applies energy in the form of light or wavelength to the negative electrode slurry S. For example, the first drying part 121 may include an ultraviolet dryer, a near infrared dryer, a far infrared dryer, an ultrasonic dryer, or the like.
[0079] As an example, the first drying part 121 may include a far-infrared dryer emitting energy having a wavelength of 1 μm or more, more specifically, 5 μm or more, 10 μm or more, or 20 μm or more, to achieve a uniform drying rate of the negative electrode slurry S. Unlike a near-infrared dryer or an infrared dryer conventionally used in the art, the far-infrared dryer has the advantage of having good energy efficiency due to the long light or wavelength, and can uniformly apply energy not only to the surface of the negative electrode slurry S but also to the inside, thereby increasing the adhesion between the negative electrode slurry S and the negative electrode collector C in a short time.
[0080] In this case, the first drying unit 121 can be 50 kW / m 2 Up to 1000kW / m 2 The power density can release energy at 50kW / m 2 Up to 500kW / m 2 、50kW / m 2 Up to 250kW / m 2 , or 50kW / m 2 and 200kW / m 2 The present invention can control the power density of the first drying component 121 within the above range, thereby preventing excessive power density from causing uneven drying of the negative electrode slurry.
[0081] In addition, the present invention can also arrange the first drying unit 121 and the second drying unit 122 at specific positions to achieve uniform and high crystal plane orientation of the carbon-based negative electrode active material contained in the negative electrode active layer.
[0082] Specifically, the first drying part 121 may be located at one side of the widthwise edge of the magnetic part (eg, the first magnetic part) on the upper portion of the negative electrode slurry so as to pre-dry the edge end S2 of the negative electrode slurry while applying the magnetic field.
[0083] In one example, if Figure 3 As shown, the first drying part 121 can be separately arranged on the edge side of the width direction (y-axis direction) of the magnet part located on the upper part of the negative electrode slurry being conveyed along the conveying direction of the electrode sheet. In this case, it is not only easy to add the first drying part 121 to the conventional equipment for manufacturing negative electrodes, but also easy to maintain and repair during use, so it has the advantage of high economic benefits.
[0084] As another example, Figure 4 As shown, the first drying part 121 can be arranged at the edge side in the width direction (y-axis direction) of the magnet part located above the conveyed negative electrode slurry along the conveying direction of the electrode sheet, but can be arranged to be mixed with the magnet part including the unit magnets 111a' and 111b' to form a row.
[0085] In this case, the unit magnets 111a', 111b' forming a row with the first drying part 121 on the edge side in the width direction (y-axis direction) of the magnet part may include magnets whose magnetic flux density (Br) is relatively less affected by temperature than the unit magnets arranged in the center in the width direction (y-axis direction) of the magnet part. The above-mentioned "magnetic flux density (Br)" refers to the density of magnetic lines of force per unit area. Generally, as the temperature increases, the magnetic flux density Br decreases and eventually loses its magnetic force, and the degree of decrease in the magnetic flux density Br is affected by the temperature coefficient of the magnetic flux density Br. Since the first drying part 121 of the present invention generates heat during the drying process at the edge end of the negative electrode slurry, the unit magnets 111a', 111b' in a row with the first drying part 121 may be composed of unit magnets whose temperature coefficient of the magnetic flux density Br satisfies a specific range, so that the magnetic flux density Br is less affected by temperature. For example, the unit magnets 111a', 111b' can be strontium-ferrite alloy magnets (temperature coefficient: about -0.18%); samarium-cobalt alloy magnets (temperature coefficient: about -0.03%); neodymium-iron-boron alloy magnets (temperature coefficient: about -0.12% to -0.09%); samarium-iron-nitrogen alloy magnets (temperature coefficient: about -0.07%); aluminum-nickel-cobalt alloy magnets (in other words, Alnico magnets, temperature coefficient: about -0.02%), etc. as unit magnets. The advantage of the present invention is that by adjusting the position of the first drying component 121 as described above, the crystal planes of the carbon-based negative electrode active material contained in the edge end S2 of the negative electrode slurry can be oriented and fixed step by step, so that the orientation performance of the carbon-based negative electrode active material is more excellent.
[0086] In addition, the first drying part 121 can be set at the edge side of the magnet part (such as the first magnet part) located above the conveyed negative electrode slurry, but set at a position a certain distance from the inlet where the electrode sheet is introduced into the magnet part and the outlet where the electrode sheet is removed.
[0087] For example, Figure 3 and Figure 4As shown, based on the point where the electrode sheet is introduced along the conveying direction of the electrode sheet, the first magnet component 110a and the second magnet component 110b can be respectively divided into a first area 111a-1 and 111b-1, where the length ratio of the magnet component is greater than 0% and less than or equal to 10%; a second area 111a-2 and 111b-2, where the length ratio of the magnet component is greater than 10% and less than or equal to 90%; and a third area 111a-3 and 111b-3, where the length ratio of the magnet component is greater than 90% and less than or equal to 100%. In this case, the first drying part 121 can be selectively disposed in the second area of the first magnet component 111a and the second magnet component 111b according to the position of the negative electrode slurry. In other words, when the negative electrode slurry is coated only on the upper surface of the electrode sheet, the first drying part 121 may be disposed in the second region 111a-2 of the first magnet part 111a; when the negative electrode slurry is coated on both sides of the electrode sheet, the first drying part 121 may be disposed in the second regions 111a-2 and 111b-2 of the first magnet part 111a and the second magnet part 111b.
[0088] When the first drying part 121 is disposed in the first regions 111a-1 and 111b-1 of the magnet component, the negative electrode slurry may be pre-dried before the crystal planes of the carbon-based negative electrode active material contained in the edge end S2 of the negative electrode slurry are arranged, so the orientation degree of the crystal planes of the carbon-based negative electrode active material may be low. In addition, when the first drying part 121 is disposed in the third regions 111a-3 and 111b-3 of the magnet component, the pre-drying time of the first drying part is significantly shorter, making it difficult to fix the oriented carbon-based negative electrode active material, and therefore, since the solvent in the negative electrode slurry is evaporated by using heat energy in the second drying part, the orientation degree may be lost.
[0089] Therefore, by setting the position of the first drying part 121 in the second region of the magnet part, the present invention can fully orient and fix the crystal plane of the carbon-based negative electrode active material contained in the edge end S2 of the negative electrode slurry.
[0090] In addition, the function of the second drying part 122 is to completely dry the entire negative electrode slurry to form a negative electrode active layer.
[0091] In this case, in order to prevent the crystal plane of the carbon-based negative electrode active material contained in the center of the negative electrode slurry from losing its orientation degree after being removed from the orientation unit 110, the second drying unit 122 may be disposed adjacent to the end of the orientation unit 110 from which the electrode sheet is removed, that is, the end of each of the magnet units 110a and 110b. Here, "the end of the orientation unit / magnet unit is disposed adjacent to the second drying unit" may refer to disposing the outlet of the orientation units 110: 110a, 110b and the inlet of the second drying unit 122 to be in contact or have a predetermined spacing distance, wherein the electrode sheet having the magnetic field applied to the negative electrode slurry is removed from the outlet of the orientation units 110: 110a and 110b, and the electrode sheet is introduced from the inlet of the second drying unit 122.
[0092] Kinetic energy is applied to the negative electrode slurry S in the direction (x-axis direction) of electrode sheet conveyance, and the crystal planes of the oriented carbon-based negative electrode active material are moved out of the orientation components 110: 110a and 110b, and when the magnetic field is removed, due to the kinetic energy generated by the electrode sheet conveyance, the arranged crystal planes are tilted and arranged at a low angle toward the negative electrode collector C. However, by arranging the ends (in other words, the outlets) of the orientation components 110: 110a and 110b adjacent to the inlet of the second drying component 122, the present invention enables the negative electrode slurry S to be introduced into the drying component 120 for drying immediately after leaving the ends of the orientation components, thereby minimizing the reduction in the orientation of the carbon-based negative electrode active material.
[0093] Here, if Figure 1 As shown, the end of the orientation component and the entrance of the second drying component 122 can be arranged to contact each other so as to have a spacing distance close to 0 mm. In some cases, they can be arranged to have a spacing distance of less than 10 mm, less than 8 mm, less than 5 mm, less than 3 mm, 0.5 mm to 5 mm, 5 mm to 10 mm, or 1 mm to 3 mm.
[0094] The present invention can prevent the loss of crystal plane arrangement of the carbon-based negative electrode active material contained in the negative electrode slurry due to excessive spacing by adjusting the spacing distance between the ends of the first magnet component 110a and the second magnet component 110b and the drying component as described above, and can also prevent the magnet components 110a and 110b from being degraded due to high temperature when being sucked into the second drying component 122.
[0095] Meanwhile, the second drying unit 122 may include a drying device for applying heat energy to completely and evenly dry the front surface of the negative electrode slurry. Such a second drying unit 122 may include, but is not limited to, any drying device conventionally used in the art, in particular, a heat dryer, a vacuum oven, a heater, etc., which may be used alone or in combination.
[0096] In addition, the second drying part 122 can also have a structure including a wall and a drying device (not shown), wherein the wall is used to block the periphery outside the inlet and outlet for introducing and removing the electrode sheet, and the drying device is used to dry the electrode sheet coated with the electrode slurry S on the inner wall of the wall.
[0097] When the electrode sheet enters through the inlet of the second drying part 122, the electrode sheet receives heat energy from the drying device at the inner wall surface of the wall. Therefore, the wall is preferably made of a heat insulating material to prevent the loss of heat energy transferred to the outside.
[0098] The negative electrode manufacturing device of the present invention has the following advantages: by having the above-mentioned structure, the carbon-based negative electrode active material contained in the edge of the negative electrode slurry has excellent crystal plane orientation, so a negative electrode with excellent overall orientation and excellent orientation uniformity of the negative electrode active layer can be manufactured.
[0099] Negative electrode for lithium secondary battery
[0100] In one embodiment, the present invention provides a negative electrode for a lithium secondary battery manufactured by the manufacturing device of the present invention, which includes: a negative electrode collector, and a negative electrode active layer, wherein the negative electrode active layer is arranged on at least one side of the negative electrode collector and contains a carbon-based negative electrode active material.
[0101] The negative electrode for lithium secondary battery of the present invention comprises a negative electrode active layer comprising a carbon-based negative electrode active material located on at least one side of a negative electrode current collector. The negative electrode active layer is a layer that reflects the electroactivity of the negative electrode, and is prepared by coating a negative electrode slurry comprising a negative electrode active material that reflects an electrochemical redox reaction during battery charge and discharge onto at least one surface of the negative electrode current collector, and then drying and rolling the negative electrode slurry.
[0102] Here, the negative electrode is characterized in that the negative electrode includes a negative electrode active layer of highly oriented and uniform carbon-based negative electrode active material by orienting and drying the crystal planes of the carbon-based negative electrode active material contained in the negative electrode slurry during the manufacturing process using the negative electrode manufacturing apparatus of the present invention described above.
[0103] Generally, the negative electrode slurry used to make the negative electrode active layer is in the form of a mixture of a carbon-based negative electrode active material and a dispersant, wherein the dispersant is generally water. Water is a solvent with a large surface tension. Due to the large surface tension of water, the negative electrode slurry contained therein will show a phenomenon of reduced surface area exposed to the air after being coated on the negative electrode current collector. Therefore, the negative electrode slurry coated on the negative electrode current collector forms a curved surface with an edge end at a predetermined angle to the surface of the negative electrode current collector inside the slurry. Due to the large surface tension of water, the curved surface causes the potential energy of the molecules near the liquid surface and the molecules inside the liquid to be different, and this energy deviation acts as a factor that hinders the orientation of graphite using a magnetic field. Therefore, generally, when a magnetic field is applied to the negative electrode slurry, the orientation of graphite is higher in the central part of the negative electrode slurry with a flat surface, while the orientation of graphite is lower in the edge end area of the negative electrode slurry with a curved surface.
[0104] However, since the negative electrode of the present invention is manufactured by the negative electrode manufacturing device of the present invention, the crystal plane of the carbon-based negative electrode active material contained in the edge end area of the negative electrode slurry has a higher arrangement angle relative to the surface of the negative electrode collector, so the overall orientation and uniformity of the negative electrode active layer are excellent.
[0105] Specifically, the negative electrode active layer of the negative electrode is divided into a flat area S1 located at the center of the width direction of the negative electrode active layer and having a uniform thickness, and a landslide area S2 located at the edge of the negative electrode active layer and having a gradient thickness. In this case, the crystal plane orientation of the carbon-based negative electrode active material contained in the flat area S1 and the landslide area S2 is high and the orientation degree is uniform, thereby satisfying the following formula 1:
[0106] [Formula 1]
[0107] 0.9≤[OI 滑坡 ] / [OI 中心 ]≤1.3
[0108] (Wherein, in Formula 1,
[0109] OI 滑坡 represents the ranking value (OI) of the landslide area,
[0110] OI 中心 Indicates the alignment value (OI) of the flat area,
[0111] The arrangement value (OI) represents the area of the peak representing the (0,0,4) crystal plane in the XRD measurement of the negative electrode active layer (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) ratio (I 004 / I 110 ).
[0112] The orientation of the crystal plane of the carbon-based negative electrode active material can be determined by crystal plane analysis of the carbon-based negative electrode active material, such as X-ray diffraction. The arrangement value (OI) of the carbon-based negative electrode active material represented by Formula 1 can be an indicator of the direction of arrangement of the crystal structure of the carbon-based negative electrode active material, and more specifically, it indicates the degree to which the crystal plane of the plane of the carbon-based negative electrode active material is arranged relative to the surface of the negative electrode current collector in an X-ray diffraction (XRD) measurement. For example, if the negative electrode active layer contains graphite as a carbon-based negative electrode active material, the X-ray diffraction measurement of the electrode sheet shows 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2° and 77.5±0.2°, representing the (0,0,2) face, (1,0,0) face, (1,0,1)R face, (1,0,1)H face, (0,0,4) face and (1,1,0) face of the graphite crystal face contained in the negative electrode active layer, respectively. Typically, in the case of graphite, the graphene layers are located on the a and b axis planes, and these graphene layers are stacked along the c axis to have a hexagonal or rhombohedral crystal structure. Here, the crystal face peak is a peak representing a characteristic face of such a crystal structure. In addition, the peak appearing at 2θ = 43.4 ± 0.2° can also be regarded as the overlap of the peaks corresponding to the (1,0,1) R plane of the carbon-based negative electrode active material and the (1,1,1) plane of the negative electrode collector (such as copper (Cu)), so it can be excluded when determining the arrangement value.
[0113] The present invention can measure the arrangement value (OI) of the carbon-based negative electrode active material by the area ratio of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane, specifically, by integrating the peak intensity to obtain the area ratio. The (0,0,4) plane appearing at 2θ=54.7±0.2° represents the thickness direction characteristics (c-axis direction characteristics) of the layered structure formed by stacking graphite layer planes, and the (1,1,0) plane appearing at 2θ=77.5±0.2° represents the planar characteristics (a / b-axis direction characteristics) of the stacked graphite layers. Therefore, the smaller the peak of the (0,0,4) plane representing the thickness direction characteristics of the graphite layer plane, the larger the peak of the (1,1,0) plane representing the planar characteristics of the graphite layer, indicating that the graphite plane is arranged at a high angle relative to the surface of the negative electrode current collector. In other words, the arrangement value (OI) may indicate that when the value is close to 0, the angle or inclination of the graphite layer plane relative to the negative electrode collector surface is close to 90°, and when the value is larger, the inclination relative to the negative electrode collector surface is close to 0° or 180°.
[0114] For example, since the crystal planes of the carbon-based negative electrode active material contained in the flat region S1 of the negative electrode active layer are arranged at a high angle relative to the negative electrode current collector, the arrangement value (OI) of the negative electrode of the present invention may be 0.1 to 1.5. Specifically, the arrangement value (OI) may be 0.1 to 1.2; 0.1 to 1.0; 0.1 to 0.5; 0.15 to 0.6; 0.15 to 0.5; 0.2 to 0.5; 0.4 to 0.7; 0.3 to 0.5; 0.4 to 0.9; 0.5 to 0.9; 0.6 to 1.0; 0.7 to 1.0; 0.9 to 1.2; or 0.8 to 1.1. An arrangement value (OI) of a carbon-based negative electrode active material of less than 1.5 means that when the carbon-based negative electrode active material contains graphite, the arrangement of the crystal plane (referring to the plane of the graphite layer) makes it have a high angle / inclination relative to the negative electrode collector, for example, an angle / inclination of more than 60°, more than 70°, 70° to 90°, 80° to 90°, 65° to 85°, or 70° to 85°.
[0115] In addition, for the negative electrode of the present invention, not only the overall arrangement value (OI) of the carbon-based negative electrode active material contained in the negative electrode active layer is low, but also the uniformity of the arrangement value (OI) is excellent, so the above formula 1 can satisfy 0.9 to 1.3 (in other words, 0.9≤[OI 滑坡 ] / [OI 中心 ]≤1.3). Specifically, the negative electrode active layer of the negative electrode may satisfy the above formula 1 as 0.9 to 1.2 (ie, 0.9≤[OI 滑坡 ] / [OI 中心 ]≤1.2); 0.9 to 1.1 (i.e. 0.9≤[OI 滑坡 ] / [OI 中心 ]≤1.1); 1.0 to 1.3 (i.e. 1.0≤[OI 滑坡 ] / [OI 中心 ]≤1.3); 1.0 to 1.2 (i.e. 1.0≤[OI 滑坡 ] / [OI 中心 ]≤1.2); 1.1 to 1.2 (i.e. 1.1≤[OI 滑坡 ] / [OI 中心 ]≤1.2); 1.2 to 1.3 (i.e. 1.2≤[OI 滑坡 ] / [OI 中心 ]≤1.3); i.e. 1.0 to 1.15 (i.e. 1.0≤[OI 滑坡 ] / [OI 中心 ]≤1.15).
[0116] Formula 1 represents a ratio of arrangement values (OI) of the carbon-based negative electrode active materials in the flat region S1 and the landslide region S2 of the negative electrode active layer, respectively, wherein the closer the ratio is to 1, the smaller the deviation is.
[0117] The negative electrode manufactured using a conventional negative electrode manufacturing device is characterized in that the arrangement value (OI 滑坡 ) is the arrangement value of the carbon-based active material contained in the flat region (OI 中心 ) is about 1.5 times of that of the negative electrode active layer. For the landslide area S2 of the negative electrode active layer, the negative electrode tab can be introduced when the negative electrode is manufactured. However, if the arrangement value (OI 滑坡 ) is higher than the arrangement value (OI 中心 ), the landslide area S2 may have lower lithium mobility and electron mobility than the flat area S1, which leads to an increase in the resistance of the negative electrode tab and a decrease in the charge and discharge characteristics of the negative electrode.
[0118] However, by adjusting the ratio of the arrangement values of the carbon-based negative electrode active materials respectively contained in the flat region S1 and the landslide region S2 to 0.7 to 1.3, the negative electrode of the present invention can minimize the deviation of the arrangement values of the carbon-based negative electrode active materials contained in the flat region S1 and the landslide region S2. Therefore, the negative electrode can uniformly realize the lithium mobility and the electron mobility in the negative electrode active layer, thereby further improving the charge and discharge characteristics of the negative electrode.
[0119] Meanwhile, the flat region S1 of the negative electrode slurry is a region from the center of the negative electrode slurry during the negative electrode manufacturing process, the exposed surface of which is flat, and has a uniform average thickness of the negative electrode active layer, and the length ratio in the width direction may be greater than 95% of the total length. The flat region is a region constituting the main body of the negative electrode active layer, and the length ratio may be more than 96%; more than 97%; more than 98%; more than 99%; more than 99.5%; 99% to 99.9%; or 99.5% to 99.99% of the total length based on the width direction of the negative electrode active layer.
[0120] Here, the "width direction of the negative electrode active layer" may refer to the direction (y-axis direction) perpendicular to the moving direction (x-axis direction) of the negative electrode collector when the negative electrode is manufactured, and may be the same as the direction from one surface of the negative electrode sheet to the opposite surface thereof in the manufactured negative electrode. The present invention can further improve the power and energy density of the lithium secondary battery including the negative electrode by adjusting the length ratio of the flat area S1 to the above range.
[0121] In addition, the landslide area S2 of the negative electrode slurry is the area from the edge of the negative electrode slurry during the negative electrode manufacturing process, and its exposed surface is arc-shaped. The average thickness of the negative electrode active layer shows a gradually decreasing gradient as it extends outward in the width direction.
[0122] In this case, the landslide area S2 can be continuously arranged on both sides of the flat area S1. In some cases, due to the punching (or grooving) of the electrode sheet during the manufacture of the negative electrode, it can also be continuously arranged on only one side of the flat area S1.
[0123] In addition, the length ratio of the landslide area S2 in the width direction of the negative electrode active layer can be less than 5% of the total length. Specifically, considering the energy density of the negative electrode, the length ratio of the landslide area S2 can be less than 4% of the overall length ratio in the width direction of the negative electrode active layer; less than 3%; less than 2%; less than 1%; less than 0.5%; 0.01% to 1%; or 0.01% to 0.5%. The length ratio is based on the overall length ratio arranged in the width direction of the negative electrode active layer. When the landslide area S2 is located on both sides of the flat area S1, the length ratio of each landslide area can be halved to 1 / 2 of the above ratio.
[0124] In addition, the landslide area S2 may have a thickness gradient in which the thickness decreases as it extends outward, so that the arc-shaped exposed surface may have a predetermined inclination angle relative to the negative electrode current collector. For example, the inclination angle of the exposed surface of the landslide area S2 relative to the negative electrode current collector may be 70° or more, more specifically, the inclination angle is 75° or more; 80° or more; 85° or more; 70° to 85°; 75° to 80°; 70° to 75°. The present invention can prevent the reversal of the N / P ratio at the end of the electrode assembly after assembly with the positive electrode by adjusting the inclination angle of the exposed surface of the landslide area S2 relative to the negative electrode current collector to the above range, and can further improve the adhesion between the negative terminal and the separator.
[0125] Further, the average thickness of the negative electrode active layer can be 100 μm to 300 μm, more specifically, 100 μm to 250 μm; or 130 μm to 190 μm, and the average thickness can be the same as the average thickness of the flat area. The present invention can adjust the average thickness of the negative electrode active layer to the above range, so that the crystal planes of the carbon-based negative electrode active material contained in each region can be evenly arranged, which can improve the high-rate charge and discharge performance and energy density of the battery containing the negative electrode.
[0126] In addition, the negative electrode active layer may have a structure in which two separate layers are stacked, depending on the battery model or product use to which the negative electrode of the present invention is applied, but is not limited thereto.
[0127] Specifically, the negative electrode of the present invention may have a structure in which a first negative electrode active layer is disposed on the negative electrode current collector, and a second negative electrode active layer is disposed on the first negative electrode active layer. At this time, the first negative electrode active layer and the second negative electrode active layer respectively contain carbon-based negative electrode active materials, and the carbon-based negative electrode active materials contained in each layer may be the same or different. The advantage of the negative electrode active layer having a double-layer structure on the negative electrode current collector is that the composition of each negative electrode active layer can be easily controlled, thereby providing the following advantages: the energy-saving active material of the battery can be used as the negative electrode active material to improve the electrical properties of the negative electrode, and to improve and / or prevent problems caused thereby (for example, the surface adhesion between the negative electrode current collector and the negative electrode active layer is poor).
[0128] In addition, the negative electrode active layer contains a carbon-based negative electrode active material as a negative electrode active material, thereby achieving electrical activity through a reversible redox reaction during the battery charge and discharge process.
[0129] The carbon-based negative electrode active material refers to a material with carbon atoms as the main component, and the carbon-based negative electrode active material may include graphite. The graphite may include one or more of natural graphite and artificial graphite.
[0130] In one example, the carbon-based negative electrode active material may include a mixed graphite containing a mixture of natural graphite and artificial graphite. In this case, the mixed graphite may be a mixture of natural graphite and artificial graphite in a weight ratio of 10 to 50:50 to 90, or 10 to 30:70 to 90. By adjusting the content ratio of natural graphite and artificial graphite as described above, the mixed graphite can prevent the adhesion of the negative electrode current collector and the negative electrode active layer from being reduced due to the weight of natural graphite being less than 10 parts by weight relative to the total weight, and can prevent the charge and discharge capacity of the negative electrode from being reduced due to the natural graphite being greater than 50 parts by weight.
[0131] In addition, the form of the carbon-based negative electrode active material is not particularly limited, but preferably a spherical graphite assembly formed by a plurality of flake graphites. As flake graphite, natural graphite, artificial graphite, calcined carbon (blocky mesophase) based on tar and asphalt, and graphitized coke (green coke, oily coke, asphalt coke, needle coke, petroleum coke, etc.) can be used. In particular, the carbon-based negative electrode active material is preferably assembled using a plurality of highly crystalline natural graphites. In addition, a graphite assembly can be formed by assembling 2 to 100 pieces, preferably 3 to 20 pieces of flake graphite fragments.
[0132] In addition, the average particle size (D 50 ) may be 0.5 μm to 20 μm. More specifically, the average particle size (D 50) may be 0.5 μm to 15 μm; 0.5 μm to 10 μm; 5 μm to 20 μm; 10 μm to 20 μm; 12 μm to 18 μm; 2 μm to 7 μm; 0.5 μm to 5 μm; or 1 μm to 3 μm.
[0133] The average particle size of graphite may advantageously have a smaller particle size to maximize the disorder of individual particles in the expansion direction, thereby preventing the particles from expanding due to the charging of lithium ions. However, when the particle size of graphite is less than 0.5 μm, a large amount of binder may be required due to the increase in the number of particles per unit volume. On the other hand, when the maximum particle size exceeds 20 μm, the expansion becomes serious, and with repeated charging and discharging, the adhesion between particles and the adhesion of particles to the current collector may decrease, and the cycle characteristics may be significantly reduced.
[0134] Further, in addition to the carbon-based negative electrode active material, the negative electrode of the present invention may also include a predetermined silicon-based negative electrode active material in the negative electrode active layer. The silicon-based negative electrode active material is a material with silicon (Si) as the main component, and may include silicon (Si) particles, silicon monoxide (SiO), silicon dioxide (SiO2) particles, silicon carbide (SiC) or a mixture thereof. In some cases, the silicon (Si)-containing particles may further include silicon carbide (SiC) particles and silicon (Si) particles, silicon monoxide (SiO) and / or silicon dioxide (SiO2) particles.
[0135] Further, for 100 parts by weight of all negative electrode active materials, the content of silicon-based negative electrode active materials may be 0.5 parts by weight to 30 parts by weight, more specifically, the content of silicon-based negative electrode active materials may be 1 part by weight to 9 parts by weight, 3 parts by weight to 7 parts by weight, 11 parts by weight to 19 parts by weight, 13 parts by weight to 17 parts by weight, 10 parts by weight to 30 parts by weight, 20 parts by weight to 30 parts by weight, 15 parts by weight to 25 parts by weight, 9 parts by weight to 22 parts by weight. The present invention adjusts the content of carbon-based negative electrode active materials and silicon-based negative electrode active materials contained in the negative electrode active materials to the above range, while improving the charging capacity per unit mass, reducing lithium consumption and irreversible capacity loss during the initial charge and discharge process of the battery.
[0136] Meanwhile, in addition to the carbon-based negative electrode active material as a main component, the negative electrode active layer of the present invention may optionally further include a conductor, a binder, other additives, etc. as needed.
[0137] The conductor may include but is not limited to one or more of the following: carbon black, such as acetylene black, Ketjen black, etc.; carbon nanotubes; carbon nanofibers, etc.
[0138] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, or the like as a conductor alone or in combination.
[0139] In this case, the content of the conductor may be 0.1 to 10 parts by weight, more specifically, 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight, based on 100 parts by weight of the total negative electrode active layer. The present invention can prevent the problem of negative electrode resistance increasing due to low conductor content and thus reducing charging capacity, and the problem of negative electrode active material content decreasing due to excessive conductor content and thus reducing charging capacity, or the problem of reducing fast charging characteristics due to increased loading of the negative electrode active layer by controlling the content of the conductor within the above range.
[0140] In addition, the binder can be appropriately applied as a component that helps the bonding of negative electrode active materials and conductors, etc. and the bonding with the current collector, as long as it does not reduce the electrical properties of the electrode. More specifically, the binder is any one or more of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF) and polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR) and fluorinated rubber.
[0141] Based on all 100 parts by weight of the negative electrode active layer, the content of the binder can be 0.1 to 10 parts by weight, more specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. The present invention can control the binder content contained in the negative electrode active layer within the above range, thereby preventing the adhesive strength of the active layer from being reduced due to low binder content, or preventing the electrical characteristics of the electrode from being reduced due to excessive binder.
[0142] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used, and in the case of copper or stainless steel, those subjected to surface treatment of carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately applied to 1 to 500 μm.
[0143] Method for manufacturing negative electrode for lithium secondary battery
[0144] In addition, in one embodiment, the present invention also provides a method for manufacturing a negative electrode for a lithium secondary battery.
[0145] Specifically, the method for manufacturing a negative electrode includes the following steps: coating a negative electrode slurry containing a carbon-based negative electrode active material on a negative electrode current collector; applying a magnetic field to the coated negative electrode slurry using the negative electrode manufacturing apparatus of the present invention; and drying the coated negative electrode slurry to form a negative electrode active layer.
[0146] The negative electrode manufacturing method of the present invention may include: coating a negative electrode slurry containing a carbon-based negative electrode active material on a negative electrode current collector, and applying a magnetic field to the surface of the coated negative electrode slurry, so that the carbon-based negative electrode active material in the negative electrode slurry is arranged at a high angle relative to the surface of the negative electrode current collector. Then, the negative electrode slurry containing the continuously arranged carbon-based negative electrode active material is dried to form a negative electrode active layer, thereby manufacturing a negative electrode.
[0147] The step of coating the negative electrode slurry is a step of coating the surface of the moving negative electrode current collector by discharging the negative electrode slurry containing the carbon-based negative electrode active material, and any method conventionally used in the art can be adopted without particular limitation, but preferably a die coating method is used. The die coating method can be performed by a slot die having a separator for controlling the discharge conditions of the negative electrode slurry. In this case, by controlling the shape of the separator, etc., the load amount, coating thickness, etc. of the negative electrode slurry coated on the negative electrode current collector can be easily controlled.
[0148] In addition, the step of forming the negative electrode active layer may be performed by applying a magnetic field to the negative electrode slurry applied using the negative electrode manufacturing apparatus of the present invention and drying it.
[0149] The magnetic field application can be performed by an orientation component of a manufacturing device disposed at the upper and lower parts of the negative electrode current collector coated with the negative electrode slurry. Here, the arrangement value (OI) of the carbon-based negative electrode active material contained in the negative electrode slurry can be adjusted by the intensity of the applied magnetic field, the time of exposure to the magnetic field, etc. Therefore, the above-mentioned magnetic field application can be performed under predetermined magnetic field intensity and time conditions.
[0150] In one example, the applied magnetic field strength may be 2000G (Gauss) to 9000G (Gauss), more specifically, 2000G to 8000G; 2000G to 7000G; 2000G to 6000G; 4000G to 9000G; 4000G to 7000G; 6000G to 9000G; 2500G to 5500G; 3000G to 5500G; 3500G to 5500G; 4000G to 5500G; 3500G to 4500G; or 4500G to 5000G.
[0151] As another example, the magnetic field may be applied for 5 seconds to 60 seconds, and more specifically, may be applied for 10 seconds to 60 seconds; 10 seconds to 30 seconds; 30 seconds to 60 seconds; 40 seconds to 50 seconds; 15 seconds to 35 seconds; or 10 seconds to 50 seconds.
[0152] For example, the magnetic field may be applied to the negative electrode slurry at an intensity of 4700±100 G for 12 to 33 seconds.
[0153] In addition, the drying time and manner of the negative electrode slurry may be different depending on the coating position of the negative electrode slurry. Specifically, the edge end of the negative electrode slurry may be pre-dried by light energy while applying the magnetic field or continuously, and then the front surface of the negative electrode slurry may be completely dried by heat energy immediately after applying the magnetic field. Since the base material for the negative electrode manufacturing device described previously is the same, a more detailed description is omitted.
[0154] In addition, the negative electrode manufacturing method of the present invention may further include a step of rolling the dried negative electrode slurry. The rolling step is a step of increasing the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roller press or the like. In this case, the rolling may be performed at a temperature higher than room temperature.
[0155] Specifically, rolling can be carried out at a temperature of 40°C to 100°C, more specifically, the temperature is 60°C to 100°C; 75°C to 100°C; 85°C to 100°C; 50°C to 90°C; 60°C to 80°C; 65°C to 90°C; 40°C to 70°C; or 40°C to 60°C.
[0156] In addition, rolling can be carried out at a rolling speed of 2m / s to 7m / s, or more specifically, at a rolling speed of 2m / s to 6.5m / s; 2m / s to 6m / s; 2m / s to 5.5m / s; 2m / s to 5m / s; 2m / s to 4.5m / s; 2m / s to 4m / s; 2.5m / s to 4m / s; 2.5m / s to 3.5m / s; 3.5m / s to 5m / s; 5m / s to 7m / s; 5.5m / s to 6.5m / s; or 6m / s to 7m / s.
[0157] In addition, the rolling may be performed under a pressure condition of 50 MPa to 200 MPa, and more specifically, the rolling may be performed under a pressure condition of 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.
[0158] The present invention can improve the energy density of the negative electrode while minimizing the change in the arrangement value of the carbon-based negative electrode active material contained in the negative electrode active layer formed by rolling the dried negative electrode slurry under the above temperature, speed and / or pressure conditions.
[0159] Hereinafter, the present invention will be described in more detail through examples and experimental examples.
[0160] However, the following embodiments and experimental examples are only used to describe the present invention, and the contents of the present invention are not limited to the following embodiments and experimental examples.
[0161] Examples 1 to 6 and Comparative Examples 1 to 2. Preparation of negative electrode for lithium secondary battery
[0162] Firstly, natural graphite and artificial graphite were prepared as carbon-based negative electrode active materials, and negative electrode slurry was prepared using the prepared carbon-based negative electrode active materials.
[0163] Specifically, the negative electrode active material was prepared by mixing natural graphite and artificial graphite in a weight ratio of 2:8, using carbon black as a conductor, carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as a binder. Then, the negative electrode slurry was prepared by mixing 95 parts by weight of the mixed graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC) and 2.5 parts by weight of styrene butadiene rubber (SBR) with water to a solid content of 50%.
[0164] After the negative electrode slurry is prepared, the negative electrode slurry (average thickness: 180 μm to 200 μm, length in the width direction: about 550 mm) is cast on a copper sheet (thickness: 10 μm, length in the width direction: about 550 mm) conveyed by roll-to-roll conveyance (conveying speed: 5 m / min) using a die coater. A magnetic field of 6000 ± 100 G is applied to the negative electrode slurry cast on the copper sheet for 15 to 30 seconds using a negative electrode manufacturing device, and a negative electrode active layer is formed by drying. Here, for the formed negative electrode active layer, the area with a length ratio of 98.5% in the width direction of the central negative electrode active layer is set as a flat area, and the area with a total length ratio of 1.5% (the length ratio of each area is 0.75%) set on both sides of the flat area is set as a landslide area. Then, the negative electrode active layer is rolled under the conditions of 50 ± 1 ° C, a pressure of 100 MPa to 150 MPa, and a conveying speed of 3 m / s to prepare a negative electrode for a lithium secondary battery.
[0165] However, the negative electrode manufacturing device for applying a magnetic field and drying the negative electrode slurry has a first magnet component and a second magnet component respectively arranged at the upper and lower parts of the copper thin plate, wherein ① the length ratio of the first magnet component and the second magnet component in the width direction relative to the length of the negative electrode slurry is adjusted as shown in Table 1.
[0166] In addition, the negative electrode manufacturing device is provided with a far-infrared dryer (power density: 150 kW / m 2 and 180kW / m 2), a first drying part including a heat dryer is provided on the outlet side of the orientation part (in other words, the first and second magnet parts). In this case, the far-infrared dryer light irradiation area of the first drying part is adjusted to the edge end of the negative electrode slurry. In addition, as shown in Table 1 below, the negative electrode manufacturing device also adjusts ② the presence or absence of the first drying part; ③ the position of the first drying part in the first magnet part (first area / second area / third area); ④ the setting form of the first drying part; and ⑤ the spacing distance between the outlet of the orientation part and the inlet of the second drying part.
[0167] [Table 1]
[0168]
[0169] Experimental example.
[0170] The orientation and orientation uniformity of the carbon-based negative electrode active material contained in the negative electrode active layer of the negative electrode of the present invention were evaluated.
[0171] Specifically, X-ray diffraction spectroscopy (XRD) was performed on the flat area and the landslide area of the negative electrode active layer of the negative electrode prepared in Examples 1 to 6 and Comparative Examples 1 and 2, and the spectrum was measured. In this case, the measurement conditions of the above X-ray diffraction (XRD) are as follows:
[0172] -Target: Cu (Kα-ray) graphite monochromator
[0173] - Slits: Divergence slit = 1°, Receiving slit = 0.1 mm, Scattering slit = 1°
[0174] -Measurement area: (1,1,0) surface: 76.5°<2θ<78.5°
[0175] (0,0,4) surface: 53.5°<2θ<56.0°
[0176] According to the spectrum measured under the above conditions, the arrangement value of the carbon-based negative electrode active material in each area is calculated according to Formula 2, and the arrangement value of the landslide area (OI 滑坡 ) and the arrangement value of the flat area (OI 中心 The results are shown in Table 2.
[0177] [Formula 2]
[0178] OI=I 004 / I 110
[0179] Among them, I 004 represents the area of the peak indicating the (0,0,4) crystal plane in the X-ray diffraction spectrum (XRD) measurement of the negative electrode active layer,
[0180] Among them, I 110 It shows the area of the peak showing the (1,1,0) crystal plane in the X-ray diffraction spectrum (XRD) measurement of the negative electrode active layer.
[0181] [Table 2]
[0182] <![CDATA[O.I 中心 ]]> <![CDATA[O.I 滑坡 / O.I 中心 ]]> Comparative Example 1 4.18 1.61 Comparative Example 2 2.62 1.55 Example 1 2.31 1.30 Example 2 1.17 1.28 Example 3 0.83 1.23 Example 4 0.71 1.22 Example 5 0.51 1.17 Example 6 0.45 1.14
[0183] As shown in Table 2, it can be seen that for the negative electrode of the lithium secondary battery of the present invention, the carbon-based negative electrode active material contained in the negative electrode active layer has excellent orientation and high orientation uniformity.
[0184] Specifically, it can be seen that the alignment value (OI) of the carbon-based negative electrode active material contained in the flat region of the negative electrode active layer of the negative electrode without the first drying component of the comparative example 中心 ) exceeds 2.5, while the ratio of the arrangement values of the flat area and the landslide area representing the orientation uniformity of the carbon-based negative electrode active material is above 1.5.
[0185] On the other hand, the arrangement value (OI) of the carbon-based negative electrode active material contained in the negative electrode active layer flat region of the negative electrode provided with the first drying component of the embodiment 中心 ) is less than 2.4, and the ratio of the arrangement values of the flat area and the landslide area representing the orientation uniformity of the carbon-based negative electrode active material is less than or equal to 1.3.
[0186] In addition, in the negative electrode of the embodiment, it was also found that when i) the length direction of the magnet part is longer than the length direction of the negative electrode slurry, ii) the first drying part is arranged in a mixed form with the unit magnet in the second region of the magnet part, and iii) the spacing distance between the orienting part and the second drying part is narrow, the planar crystal planes of the carbon-based negative electrode active material contained in the negative electrode active layer are uniformly arranged at a high angle close to vertical relative to the negative electrode current collector.
[0187] From these results, it can be seen that the negative electrode manufacturing device of the present invention can achieve high orientation of the crystal plane of the carbon-based negative electrode active material contained in the landslide area of the negative electrode active layer, so that a negative electrode with excellent overall orientation and orientation uniformity of the negative electrode active layer can be manufactured. In addition, it can also be found that the manufactured negative electrode has uniform and excellent lithium mobility and electron mobility of the negative electrode active layer, thereby having excellent charge and discharge performance.
[0188] As described above, the present invention has been described in more detail through the drawings and embodiments. However, since the configuration described in the drawings or embodiments described herein is only one embodiment of the present invention and does not represent the overall technical spirit of the present invention, it should be understood that the present invention covers various equivalents, modifications and substitutes at the time of filing this application.
[0189] Therefore, the technical scope of the present invention is not limited to the contents described in the detailed description of the specification, but should be defined by the claims of the patent.
[0190] [Explanation of Reference Numerals]
[0191] 10: Negative electrode manufacturing device
[0192] 20: Transmission components
[0193] 30: Coating parts
[0194] 110: Orientation components
[0195] 110a and 110b: first magnetic component and second magnetic component
[0196] 111a and 111b: Multiple unit magnets
[0197] 112a and 112b: Supporting parts
[0198] 120: Drying parts
[0199] 121: First drying part
[0200] 122: Second drying part
[0201] S: negative electrode slurry
[0202] S1: Flat area of negative electrode slurry
[0203] S2: Landslide area of negative electrode slurry
[0204] G: Carbon-based negative electrode active materials
[0205] C: negative electrode current collector
[0206] M: Magnetic field
[0207] E: Light Energy
[0208] 111a-1 and 111b-1: the first region of the first magnetic component and the second magnetic component and / or the unit magnet contained in the first region
[0209] 111a-2 and 111b-2: the second regions of the first magnetic component and the second magnetic component and / or the unit magnets contained in the second regions
[0210] 111a-3 and 111b-3: the third region of the first magnetic component and the second magnetic component and / or the unit magnet contained in the third region
[0211] 111a' and 111b': unit magnets forming a row with the first drying part at the edge side of the second area of the first magnetic part and the second magnetic part
Claims
1. A negative electrode manufacturing device for a lithium secondary battery, comprising: an orientation member for applying a magnetic field to an upper portion and a lower portion of an electrode sheet having a surface coated with a negative electrode slurry containing a carbon-based negative electrode active material; and A drying component, the drying component is used to dry the negative electrode slurry of the electrode sheet to which the magnetic field is applied by the orientation component; in, The drying component comprises a first drying component and a second drying component, and The first drying component pre-dries the edge of the negative electrode slurry when the orientation component applies a magnetic field to the electrode sheet, and The second drying unit dries the entire surface of the negative electrode slurry after the magnetic field application of the orientation unit is completed.
2. The negative electrode manufacturing device for lithium secondary battery according to claim 1, wherein: The orientation component includes a first magnetic component arranged on the upper part of the electrode sheet and a second magnetic component arranged on the lower part of the electrode sheet. The first magnet component and the second magnet component include a plurality of unit magnets arranged along a conveying direction and a width direction of the electrode sheet.
3. The negative electrode manufacturing device for lithium secondary battery according to claim 2, wherein: The length of the first magnet member and the second magnet member along the conveying direction of the electrode sheet is 0.5 m to 10 m.
4. The negative electrode manufacturing device for lithium secondary battery according to claim 2, wherein: The ratios of the lengths of the first magnet member and the second magnet member in the width direction are respectively 105% to 150% based on the length of the negative electrode slurry in the width direction.
5. The negative electrode manufacturing device for lithium secondary battery according to claim 2, wherein: The first drying component is disposed alone at a widthwise edge of the magnet component along the conveying direction of the electrode sheet, or is mixed with unit magnets and arranged in a row at a widthwise edge of the magnet component.
6. The negative electrode manufacturing device for lithium secondary battery according to claim 5, wherein: The first magnet component and the second magnet component are divided based on the point where the electrode sheet is introduced along the conveying direction of the electrode sheet: a first region in which the length ratio of the magnet components is 0% to 10%; A second region in which the length ratio of the magnet components is 10% to 90%; and A third region, wherein the length ratio of the magnet components is 90% to 100%, The first drying component is disposed in the second area of any one of the first magnetic component and the second magnetic component.
7. The negative electrode manufacturing device for lithium secondary battery according to claim 1, wherein: The first drying component includes at least one of an ultraviolet drier, a near infrared drier and a far infrared drier.
8. The negative electrode manufacturing device for lithium secondary battery according to claim 1, wherein: The second drying part is disposed adjacent to an end of the orientation part that removes the electrode sheet to which the magnetic field is applied.
9. The negative electrode manufacturing device for lithium secondary battery according to claim 1, wherein: The second drying unit comprises one or more of a thermal dryer, a vacuum oven and a heater.
10. A negative electrode for a lithium secondary battery manufactured by the negative electrode manufacturing device according to claim 1, comprising: a negative electrode current collector; and A negative electrode active layer is disposed on at least one side of the negative electrode current collector and contains a carbon-based negative electrode active material.
11. The negative electrode for a lithium secondary battery according to claim 10, wherein The negative electrode active layer is divided into: a centrally located flat area of uniform thickness; and a landslide zone located at the edge of the negative electrode active layer and having a thickness gradient; Wherein, the flat area and the landslide area may satisfy the following formula 1: [Formula 1] 0.9≤[OI 滑坡 ] / [OI 中心 ]≤1.3 Among them, in formula 1, OI 滑坡 represents the ranking value of the landslide area, OI 中心 represents the ranking value of the flat area, Wherein, all the arrangement values represent the area of the peak representing the (0,0,4) crystal plane in the XRD measurement of the negative electrode active layer. 004 The area of the peak representing the (1,1,0) crystal plane I 110 The ratio I 004 / I 110 .
12. The negative electrode for a lithium secondary battery according to claim 11, wherein The arrangement value OI of the flat area of the negative electrode active layer 中心 0.1 to 1.
5.
13. The negative electrode for a lithium secondary battery according to claim 11, wherein The flat area of the negative electrode active layer accounts for more than 95% of the total length of the negative electrode active layer in the width direction, and The ratio of the landslide area of the negative electrode active layer to the total length of the negative electrode active layer in the width direction is less than 5%.
14. The negative electrode for a lithium secondary battery according to claim 10, wherein: The carbon-based negative electrode active material includes at least one of natural graphite and artificial graphite.
Citation Information
Patent Citations
Standing desk that can be height-adjustable and can also be used as a chair
KR1020230032299A